1997
DOI: 10.1086/513646
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant Hepatitis During Herpes Simplex Virus Infection in Apparently Immunocompetent Adults: Report of Two Cases and Review of the Literature

Abstract: Two apparently immunocompetent adult patients developed acute fulminant hepatitis during presumptive primary herpes simplex virus type 1 (HSV-1) infection without any visible mucocutaneous lesions. HSV hepatitis was not suspected in the case of patient 1, who died without treatment. Patient 2 was empirically treated with acyclovir because of the triad of high fever, leukopenia, and markedly elevated levels of aminotransferases, and this patient survived. Most immunocompetent patients with fulminant HSV hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 17 publications
2
45
0
2
Order By: Relevance
“…Most of the case studies have demonstrated marked elevations of transaminases with AST > ALT (up to 1000-fold). Leukopenia is also a common finding in HSV hepatitis [3][4][5][6][7]. In our case, the leukopenia and the thrombopenia are likely due to myelosuppression caused by the chemotherapy with docetaxel and cisplatin.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Most of the case studies have demonstrated marked elevations of transaminases with AST > ALT (up to 1000-fold). Leukopenia is also a common finding in HSV hepatitis [3][4][5][6][7]. In our case, the leukopenia and the thrombopenia are likely due to myelosuppression caused by the chemotherapy with docetaxel and cisplatin.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, HSV hepatitis should be suspected in immunocompromised hosts with anicteric hepatitis and marked elevation of transaminases, fever and leukopenia. Mucocutaneous lesions are not necessarily part of the diagnosis, as over 40% of patients will not have identifiable oral or genital lesions or a prior history of HSV infection [3,6,7]. Physicians need to be aware of the clinical abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although HSV infection may present with mild nonspecific viral symptoms, most HSV infections are asymptomatic. Only 30%-50% show characteristic herpetic skin lesions [2][3][4] . Fulminant HSV hepatitis is a rare presentation of HSV infection and accounts for only 1% of all acute liver failure cases and 2% of all viral causes of acute liver failure 4.…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of HSV-induced hepatitis is difficult because clinical suspicion is often low, especially in immunocompetent patients. In addition, mucocutaneous lesions have been seen in only 44% of immunocompetent patients; therefore, their absence cannot rule out disease [11]. However, early diagnosis is essential because the course of HSV-induced hepatitis is rapid and fatal.…”
Section: Discussionmentioning
confidence: 99%